2017
DOI: 10.1007/s10792-017-0443-4
|View full text |Cite
|
Sign up to set email alerts
|

A case study of ciliary detachment with primary pulmonary hypertension

Abstract: The elevated venous pressure in PPH is responsible for decreased choroidal backflow and reduced venous blood outflow from the eye. PPH would contribute to the clinical manifestations of severe choroidal detachment and peripheral retina effusion in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…14 Moreover, fundus abnormalities, including tortuous retinal vessels, retinal hemorrhage, macular edema, and CSC-like changes, were observed during the dilated fundus examination in Group 1 subjects. 15 In our cases, the main ocular manifestations are shown in Table 2.…”
Section: Patient Characteristicsmentioning
confidence: 76%
“…14 Moreover, fundus abnormalities, including tortuous retinal vessels, retinal hemorrhage, macular edema, and CSC-like changes, were observed during the dilated fundus examination in Group 1 subjects. 15 In our cases, the main ocular manifestations are shown in Table 2.…”
Section: Patient Characteristicsmentioning
confidence: 76%
“…9 A few cases reported that idiopathic pulmonary hypertension can also cause ciliochoroidal effusion, which deserves further study for the pathogenesis of choroidal detachment in PAH patients in the future. 10…”
Section: Discussionmentioning
confidence: 99%
“…Dies ist umso bedenklicher, da jede getroffene Maßnahme gewürdigt werden sollte, bevor Rückschlüsse auf mögliche Arzneimittelinteraktionen von Leuprorelin gezogen werden. Insbesondere weise ich darauf hin, dass es Fallberichte zu Aderhautamotiones im Rahmen einer pulmonalen Hypertension gibt [6][7][8][9], einem Krankheitsbild, das bei einem 85-jährigen Patienten mit arteriellem Gefäßverschluss an einem Auge durchaus wahrscheinlich ist.…”
unclassified